Efektifitas Perawatan Metode Kangguru Menggunakan Jarik Terhadap Berat Badan dan Suhu BBLR: The Effectiveness of the Kangaroo Method Using Fingers for Body Weight and Temperature of LBW - Reffilyn Mithraqah Azis; Tia Nurhanifah Nurhanifah; Resa Nirmala Jona (Journal of Holistics and Health Sciences (JHHS), 2023)
LBW is the biggest contributor to neonatal mortality in Indonesia. Whereas in Demak Regency in 2021 there will be 19738 births, 3% of which will experience LBW. This result has increased compared to 2019 which was only 2.2%. LBW are at risk of experiencing cognitive development disorders, mental retardation, susceptible to infection which can cause pain and even death, so there is a need for intervention in the treatment of LBW, one of which is the kangaroo method with jarik treatment. The purpose of this study was to determine the effectiveness of the kangaroo treatment method with jarik on body weight and temperature in low birth weight infant. This type of research is a quasi-experimental design with “one group pretest-posttest design. The population in this study were Low Birth Weight Infant born at Sunan Kalijaga Hospital, Demak in June 2022. The sampling technique was purposive sampling and obtained a total sample of 20 Low Birth Weight Infant. The instrument used in this study was an observation sheet. Data analysis was carried out univariate and bivariate (using the Wilcoxon test). The results of this study found that the kangaroo method of care using jarik was effective in increasing body weight in low birth weight infant (p-value = 0.000) with an average weight gain of low newborns Low Birth Weight Infant 42,9 grams. Kangaroo mother care using a support binder (jarik) is effective in increasing the temperature of low birth weight infant p-value = 0.000) with an average increase in temperature of low birth weight infant of 0.30C. Suggestions are that health services can improve the ability of health workers in carrying out kangaroo care methods, so as to be able to provide in-house training for mothers so that they can be done at home, given the many benefits of this method for both mother and baby, it is hoped that further researchers can develop this research with other methods. ABSTRAK BBLR merupakan penyumbang terbesar kematian neonatal di Indonesia. Sedangkan di Kabupaten Demak pada tahun 2021 terdapat 19738 kelahiran 3% diantaranya mengalami BBLR. Hasil tersebut mengalami peningkatan dibandingkan pada tahun 2019 yang hanya sebesar 2.2%. BBLR beresiko mengalami gangguan perkembangan kognitif, retardasi mental, mudah mengalami infeksi yang dapat mengakibatkan kesakitan bahkan kematian, sehingga perlu adanya intervensi dalam penanganan BBLR salah satunya yaitu perawatan metode kanguru dengan jarik. Penelitian ini bertujuan untuk mengetahui efektifitas perawatan metode kangguru dengan jarik terhadap berat badan dan suhu BBLR. Jenis penelitian ini adalah quasi eksperimen dengan rancangan “one group pretest-posttest design”. Populasi dalam penelitian ini adalah BBLR yang lahir di RSUD Sunan Kalijaga Demak pada bulan Juni 2022 dengan teknik purposive sampling dan didapatkan jumlah sampel sebesar 20 bayi BBLR. Instrumen yang digunakan adalah lembar observasi. Analisis data dilakukan dengan menggunakan uji Wilcoxon. Hasil penelitian ini didapatkan bahwa perawatan metode kangguru menggunakan jarik efektif meningkatkan berat badan sebesar 42,9 gram dengan pvalue 0,000 dan meningkatkan suhu badan sebesar 0,30C dengan pvalue 0,000 dalam waktu 3 hari. Saran diharapan pelayanan kesehatan bisa meningkatkan kemampuan petugas kesehatan dalam melakukan perawatan metode kangguru, sehingga mampu memberikan in house training bagi ibu agar dapat dilakukan dirumah, mengingat banyaknya manfaat metode ini baik pada ibu dan bayinya, diharapkan peneliti selanjutnya bisa mengembangkan penelitian dengan metode yang lain.